Secondary Powers vis-à-vis South Africa: Hard Balancing, Soft Balancing, Rejection of Followership, and Disregard of Leadership - Sören Scholvin (German Institute of Global and Area Studies (GIGA), 2017)
The second-most powerful states in regional hierarchies - or "secondary powers" - can be expected to contest against hegemons. In this paper, I assess the power that secondary powers in sub-Saharan Africa wield vis-à-vis South Africa and suggest that their intended and unintended contestation can be captured as hard balancing, soft balancing, rejection of followership, and disregard of leadership. Angola's foreign policy is marked by a mix of these types of contestation and a recent shift towards soft balancing, which results from Angola's increasing economic influence in some regional countries. Kenya might reject followership or even hard-balance in economic affairs but has not done so yet. Nigerian-South African relations are characterised by a disregard of South African leadership, especially in security policy, and unintended economic soft balancing.
Keywords: 300; balancing; contestation; regional powers; secondary powers; Angola; Kenya; Nigeria; South Africa